O12 Effect of rituximab on RA-associated bronchiectasis and comparison of 5-year respiratory survival with TNFi. (20th April 2020) - Yuzaiful, Md; Yusof, Md; Iqbal, Kundan; Darby, Michael; Lettieri, Giovanni; Vital, Edward M; Beirne, Paul; Dass, Shouvik; Emery, Paul; Kelly, Clive
Abstract: Background: Bronchiectasis (BR) is a significant pulmonary morbidity common in people with rheumatoid arthritis (RA). Patients with RA and bronchiectasis (RA-BR) often have severe arthritis but the use of biologics may be difficult in this group of patient due to concerns over safety. There is no data comparing the use of rituximab (RTX) and tumour necrosis factor inhibitors (TNFi) in RA-BR. The objectives of this study were to evaluate effect of rituximab (RTX) in patients with RA-BR and compare 5-year respiratory survival between those treated with RTX and TNFi. Methods: A retrospective observational cohort study of RA-BR was conducted in RTX or TNFi-treated RA patients from two UK centres over 10 years. Identical data collection methodologies were used between centres. BR was assessed using number of infective exacerbations/year. Respiratory survival was defined as time from therapy initiation to discontinuation either due to lung exacerbation or lung-related deaths. Results: Of 800 RTX-treated RA patients, 68 had RA-BR (prevalence=8.5%). Post-RTX, new BR was diagnosed in 3/735 patients (incidence=0.4%). At 12 months post-Cycle 1 RTX, 21/68 (31%) patients had fewer exacerbations than the year pre-RTX, 36/68 (53%) remained stable and 11/68 (16%) had increased exacerbations. Pseudomonas colonisation at RTX baseline was associated with increased risk of this initial exacerbation [OR 7.23 (95% CI 1.28-40.80)] while older age reduced risk [OR 0.44 (95% CI 0.21-0.90) per 10 years of age]. The rates of exacerbation improved after Cycle 2 RTX and were stable up to 5 cycles. Of patients who received ≥2 RTX cycles (n = 60), increased exacerbations occurred in 7/60 (12%) and were associated with low IgG, aspergillosis and concurrent alpha-1-antitrypsin deficiency. Respiratory survival was compared between RA-BR patients treated with RTX (N = 68) or TNFi (N = 46). Most characteristics were matched between these two groups. However, median (IQR) number of infective exacerbations/year in the previous 12 months pre-bDMARDs was higher in those treated with RTX than TNFi; 3.0 (1-4) and 0 (0-2) respectively. Overall, 8/68 (11.8%) patients discontinued RTX while 15/46 (32.6%) discontinued TNFi due to respiratory causes. Moreover, the 5-year respiratory survival was better in RTX-treated compared to TNFi-treated RA-BR patients; HR 0.40 (95% CI 0.17-0.96); p = 0.041, adjusted for age, gender and centre effect. Distribution of TNFi in those who discontinued therapy due to respiratory causes was etanercept=6, infliximab=6, adalimumab=2 and certolizumab=1. Conclusion: The majority RA-BR patients had stable or improved pulmonary symptoms during RTX therapy over a prolonged follow-up period. In isolated cases, worsening of exacerbation after RTX therapy had definable causes. Despite a higher rate of exacerbations pre-biologic, rates of discontinuation or deaths due to respiratory causes were better for RTX than a matched TNFi cohort. RTX appears to be an acceptable therapeutic choice for RA-BR if a biologic is needed. Disclosures: M. Md Yusof: None. K. Iqbal: None. M. Darby: None. G. Lettieri: None. E. Vital: Honoraria; Roche. Grants/research support; Roche. P. Beirne: None. S. Dass: Honoraria; Roche. P. Emery: Consultancies; Pfizer, MSD, Abbott. Grants/research support; Roche, Pfizer, MSD, Abbott. C. Kelly: Consultancies; Boehringer-Ingelheim. Honoraria; Boehringer-Ingelheim.